The diffusion of Max condoms among young women in KwaZulu Natal - Donald, Charlene Chenaye (Rhodes University, Faculty of Commerce, Rhodes Business School, 2019)
HIV is a disease that has a myriad of effects across different settings, and its prevalence varies across countries with different epidemiological drivers. The growing and disproportionate impact on young women has encouraged new ideas in HIV prevention strategies. The profusion of studies on HIV prevention strategies notwithstanding, the aspect of condom innovation has been largely ignored in literature. Drawing on the Diffusion of Innovation theory, this study examines how Max condoms have gained popularity among young women aged 18-24 years. The hypotheses are tested using an innovation-decision conceptual model and a comprehensive data set of 131 participants from rural, peri-urban and urban districts in KwaZulu Natal. Results reveal that the impact of marketing material and an effective public launch were significant in increasing Max condoms uptake, while the influence of peers and other members of one's social system are critical for normalising the behaviour change. Young women have adopted Max condoms and uptake is continually influenced by positive perception of Max condoms' relative advantage.
Keywords: Uncatalogued